Hyperlocal Restaurants: The Intersection of Food Service, Agriculture, and Public Health. - Sirsat, Sujata A. (Journal of Environmental Health)
There is a paucity of literature connecting food service, agriculture, and public health with hyperlocal restaurants. The goal of this study was to explore this intersection by conducting semistructured interviews (N = 11) with hyperlocal restaurateurs and public health officials until data saturation was met. The interview results suggest that hyperlocal restaurateurs have a deep passion for their vocation and community. Results show that the restauranteurs were invested in providing the best quality and value to customers, even though their perception was that customers were wary of the associated cost. Results from both restaurateurs and public health officials also show that health inspectors do not ask about farm operations. This finding is consistent with Texas Administrative Code 229.210, which states that health inspectors cannot address any item from the farm unless there is a known adulteration (Texas Administrative Code, 2023). Suggestions and tools for practitioners and public health officials are included in this article.